Peran Guru PAI dalam Meningkatkan Penghayatan dan Pengamalan Ibadah pada Peserta Didik - Ervina Dwi Apreliani; M.Asep Fathur Rozi (Journal on Education, 2024)
This research aims to determine the extent to which roles, strategies and factors influence PAI teachers in increasing the appreciation and practice of worship among students at SDN Krandegan. The role of PAI teachers is not only to teach but also to increase students' religious beliefs, especially in worship. Method used is a descriptive qualitative approach with data collection techniques using observation or direct observation, interviews and documentation. With resource persons from the school principal, and PAI teachers at SDN Krandegan, Gandusari sub-district, Trenggalek district. Thie riesults of the research shiow thati PAI teachers havei playedi an optimal and quite good role in increasing the appreciation and practice of worship among students. This can be seen from his role as a motivator, providing a role model, advising students and as a liaison between the school and parents. By using strategies in the form of habituation and approaches to students. As well as factors that influence PAI teachers, namely the school environment and student awareness.